Uncovering Peripheral Organ Defects in Spinal Muscular Atrophy: Insights from AAV9-SMN Gene Therapy - Reilly, Aoife (Université d'Ottawa / University of Ottawa, 2025)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease characterized by motor neuron loss and skeletal muscle atrophy. SMA is caused by the loss of the SMN1 gene and low SMN protein levels. Although lower motor neurons are a primary target, there is evidence that peripheral organ defects contribute to SMA. Motor neurons are nevertheless considered the primary target for treatment, and therapies directed to the central nervous system (CNS) are used on SMA patients and in clinical trials. Here, we aimed to explore the contributions of the peripheral organs to SMA by first performing a systematic characterization of the peripheral and neuronal defects in the Smn²ᴮᐟ⁻ mouse model of SMA and then comparing the rescue effect of either intravenous (IV) or intracerebroventricular (ICV) delivery of scAAV9-cba-SMN on the mice. Smn²ᴮᐟ⁻ mice displayed several peripheral defects prior to motor neuron loss. ICV injections increased SMN in peripheral organs and the CNS while IV administration increased SMN in peripheral tissues only, largely omitting the CNS. Further, ICV injections provided better motor neuron and motor function protection. Surprisingly, both delivery routes resulted in an equal long-term rescue effect on survival, weight, and peripheral defects. These results demonstrate the early and independent contributions of the peripheral organs to SMA pathology. Our work also emphasizes a need for a holistic approach to SMA management, including treatments that target motor neuron-independent pathways and the use of a set of biomarkers that monitors multiple systems.
Keywords: spinal muscular atrophy